Local Industry Transformation through ESG: Evidence from Bone Regency on Policy Impact, Business Competitiveness and Sustainability - Asdar, Asdar; Hazan, Hazan; Masriadi, Masriadi; Muslimin, Muslimin; Yunus, Andi Muhammad (Jurnal Ilmiah Administrasi Publik dan Pemerintahan (JIAPP), 2025)
This study analyzes the impact of implementing Environmental, Social, and Governance (ESG) principles on local industrial transformation in Bone Regency, South Sulawesi, focusing on business competitiveness and sustainability. The study addresses a critical research gap by examining ESG in small-scale rural industries, a context underexplored compared to studies on large corporations. A qualitative approach with a case study design was used to understand the dynamics of change in small-scale fisheries and agriculture-based industries. Data was collected through in-depth interviews, field observations, and policy document reviews, involving 18 informants from business actors, government officials, community facilitators, and local academics. The study identified six key themes: improved operational efficiency and market access; changes in perceptions and the image of the local industry; infrastructure and technological limitations; low literacy and human resource capacity; multi-stakeholder collaboration strategies; and social innovation and product diversification. Findings indicate that ESG adoption drives production efficiency, expands market opportunities, enhances community pride, and fosters locally-based innovation. However, limited facilities, sustainability literacy gaps, and coordination among actors remain significant obstacles. These findings provide both theoretical contributions—by contextualizing ESG in rural community industries—and practical implications for policymakers seeking to design adaptive, inclusive, and collaborative sustainability frameworks. The study concludes that a bottom-up, community-driven approach, reinforced by supportive policies and cross-sectoral collaboration, is essential for ensuring the long-term sustainability of local industries in Indonesia’s rural regions.